Optimization of naringinase production by Rhizophus stolonifer in solid state fermentation media using paddy husk as support - Karuppaija, S.; Kapilan, R.; Seevaratnam, V. (University of Jaffna, 2016)
The palmyrah (Borassus flabellifer L) tree represents a major socio economic factor in tropics. The economic value of the tree is reduced by fruit pulp, due to the bitter compound present in the fruit pulp but it can be hydrolyzed by the usage of naringinase enzyme. Hence this enzyme plays a key role in the food industry and pharmaceuticals for its debittering nature. Some microbes like bacteria and fungiare involved in the natural production of cost effective naringinase. The aim of this work was to optimize the cultivation conditions and the media to produce naringinase by solid state fermentation of Rhizophus stolonifer, using paddy husk as the support. The highest enzyme activity was obtained on the 7th day of incubation. Highest naringinase enzyme activity (57.97U/g DM) was obtained on the 7th day of incubation and after that activity started to decline. The enzyme activity (212.885U/g DM) obtained with 0.75% naringin concentration was significantly higher than that of other naringin concentrations tested. When the regular medium (0.5% glucose) was replaced with (w/v) 1.5% glucose and 1.5% sucrose, the enzyme activity obtained with 1.5% of glucose (484.96U/g DM) was significantly higher than that of 1.5% sucrose (238.88U/g DM). When naringinase activity was tested with different glucose concentrations, activity obtained with 1.5% of glucose concentration was significantly higher than that of other concentrations. Among the nitrogen sources tested, when 0.5 % ammonium nitrate was used significantly higher naringinase was produced by Rhizophus stolonifer than any other sources and their concentrations. The cost to produce 1073.97U/g DM was reduced by 20.15% when conditions and media composition are optimized when compared to the basal medium(57.97U/g DM). Therefore when naringinase was produced by Rhizophus stoloniferunder optimized condition, the production cost was marginally reduced.